Development administration : theory and practice - Sharma, R.D (Delhi, 1992)
"Development" has become inescapable for developing societies. Every government and political party in power cannot sustain long er without ensuring an agreeable rate of growth of economy and acceptable standard of life. Socio-economic transformation can not be judged by simple and "mischievous" indicators of per capita income etc.
Keywords: Development administration